Saetaspongia sponges from the Cambrian (Stage 4) Balang Formation of Guizhou, China. (September 2021) - Ling, Chenchen; Peng, Jin; Zhang, Hui; Wang, Yifan; Shao, Yunbin; Sun, Quanyi; Wang, Qiujun
Abstract: Saetaspongia so far cannot be confidently assigned to any class-level crown group. Clarifying its phylogenetic position requires new information provided by more detailed studies of previously described and/or new material. Some sponge fossils with the typical skeletal architecture of Saetaspongia have recently been recognized in the Cambrian (Stage 4) Balang Biota of Guizhou, China, including S . jianhensis new species and S . cf. S . densa . The new taxon is characterized by the following features: spicules are fine monaxons and are inclined to be loosely to densely arranged into plumose arrays; skeleton is composed primarily of one major plumose bundle, with an uncertain number (perhaps two) of small plumose arrays; and primary skeleton is occasionally interspersed with some irregularly oriented individual spicules. An additional specimen consisting of large monaxons, with plumose structures and overlying irregular coarse monaxons, closely fits the description and illustrations of previously described S . cf. S . densa . By combining information from previous studies and the present research, fossil evidence indicates that the plumose architecture is a critical feature diagnostic of Saetaspongia and that there are no hexactine-based spicules in this genus. The new material from the Balang Biota further supports the notion that Saetaspongia has a protomonaxonid rather than a hexactinellid affinity. Fossil evidence suggests that Saetaspongia had a wide biogeographic distribution during the early Cambrian and the stratigraphic distribution of this genus extends up to Stage 4. UUID: http://zoobank.org/e9ca5e4a-134c-4daa-9266-19085e32614f .